Stable Interface between Lithium and Electrolyte Facilitated by a Nanocomposite Protective Layer. Issue 3 (20th January 2020) - Yang, Luyi; Song, Yongli; Liu, Hao; Wang, Zijian; Yang, Kai; Zhao, Qinghe; Cui, Yanhui; Wen, Jiayun; Luo, Wei; Pan, Feng
Abstract: Recently, solid‐state lithium batteries (SSLBs) have been considered an ideal solution for the practical application of lithium (Li) metal batteries owing to the excellent safety features of solid‐state electrolytes (SSEs). Among various SSEs, Na superionic conductor (NASICON)‐type Li1+ x Al x Ti2− x (PO4 )3 (LATP) holds great potential for its high ionic conductivity, low costs, and high stability. However, LATP tends to be reduced by metallic Li upon contact, posing a major challenge. Herein, a novel coating strategy is proposed to form a nanocomposite protecting layer on Li metal within 30 s. Such a protecting layer not only acts as an artificial solid‐electrolyte interface to conduct Li ion transportation that remains stable after repeated cycling but also effectively precludes the interfacial reaction between Li and LATP by inhibiting the interfacial electron transfer. As a result, the Li/LATP/Li symmetric cells exhibit excellent cycling stability for over 300 h of continuous Li plating/stripping. The assembled full‐cell using coated Li also shows high capacity retention after 500 cycles. Overall, this study demonstrates a facile and transferable method to reduce the reactivity of Li metal anode toward solid electrolytes with relatively high reduction potentials. Abstract : A facile and rapid coating strategy is proposed to form a robust nanocomposite protecting layer on Li metal. This layer serves as an artificial solid‐electrolyte interface that remains stable after repeated cycling. As a result, the coated Li exhibits excellent stability with Li1.3 Al0.3 Ti1.7 PO4 solid electrolyte by inhibiting the interfacial reaction interface, therefore, excellent cycling stability is obtained.